7A.08: EXPERIMENTAL STUDY TO EVALUATE THE EFFECT OF A PEPSIN EGG WHITE HYDROLYSATE ON CARDIOMETABOLIC COMPLICATIONS IN DIET INDUCED OBESE RATS. (June 2015) - Moreno, S.; Garcés-Rimón, M.; Gonzalez, C.; Vera, G.; Herradón, E.; López-Miranda, V.; Miguel, M.
Abstract : Objective: In this work we evaluated the effect of the administration of a pepsin egg white hydrolysate (HEW) on some cardiometabolic complications developed in diet induced obese rats. Design and method: 20 male 8-week-old Wistar were divided into two groups that were given until the 20th week of life the following solid and drinking fluids: high fat diet + dextrose 25% in water (O), high fat diet + (dextrose 25% + 1 g/kg/day of HEW) in water (O-HEW). Body weight and solid and liquid intakes were weekly measured. Last week, the presence of allodynia (a sign of peripheral neuropathy) was assessed using a series of calibrated Von Frey hairs. At the end of the study, direct blood pressure was measured, and after different organs and blood samples were collected to determine the effect of the hydrolysate on lipid metabolism, oxidative stress and glycemia Results: The consumption of HEW attenuated the body weight gain, decreased the abdominal perimeter and the size of epidydimal adipose tissue in O-HEW group. Moreover, the plasma malondialdehyde levels were reduced after administration of HEW in obese animals. The hyperglycemia and allodynia developed in these animals were also improved after intake of HEW. The results also showed that the consumption of HEW restored the autonomic imbalance observed in diet induced obesity. Conclusions: In conclusion, HEW, consumed directly or added to other foods, may affect simultaneously several functions in the organism, and may offer a therapeutic approach to control the different complications linked to obesity condition.